Panoramic radiography as an early screening for eagle syndrome with orofacial pain: a case report - Hanafi, Eva Yulianti; Pramanik, Farina; Ramadhan, Fahri Reza (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: The purpose of this case report was to report the findings of styloid process morphology in patients with orofacial pain. Case Report: A 39-year-old man came to a private hospital with complaints of a headache near the ear. After taking a panoramic photograph, a change in the size of the styloideus processes was obtained. The styloideus processes were elongated on the right and left sides. The elongated styloid process may be symptomatic in many cases. Examination with panoramic radiographs as support can show this syndrome quite well because it shows the styloideus process bilaterally. The elongated styloideus process seen on the panoramic radiograph can be interpreted as Eagle Syndrome. Conclusion: Elongation of the styloideus process can cause orofacial pain. The image of an elongated processus styloideus can be seen in the results of a panoramic radiograph.